Proficiency in Arabic writing skills among students at international private schools in Dubai - Abdul Jabar, Mohd Azidan; Ahmad Hatem, .; Wan Sulong, Wan Muhammad (Universiti Sultan Zainal Abidin, 2024)
The aim of the current research is to investigate the degree to which private international school students are able to write in the Arabic language. Therefore, the research relied on the mixed approach, considering that it is the most appropriate approach to achieve the research objectives and answer its questions. The sample consisted of (80) male and female students from the seventh, eighth, and ninth grades at Deira International School, and a questionnaire was used to collect data. The number of questionnaire items is (16) distributed in four components. The research reached a number of results, including: The degree of ability of writing skills in the Arabic language by private international school students was moderate. The component 1 (the ability to understand and read) came in first place, with a high degree of agreement, and with a mean of (2.49). While component 4 (producing ideas and organizing their writing) came in last place, with a moderate degree of agreement, and mean of (1.81). This means that students in international schools cannot express their feelings well in the Arabic language, which indicates an urgent need to redouble efforts in teaching them the Arabic language, especially writing skills. The research recommends training students to read sentences, structures, and texts by heart, giving them intensive training in writing skills, and putting appropriate movements on words by giving them enrichment lessons and additional jobs.